2020
DOI: 10.1590/0103-6440202003268
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cleanser Solutions on the Retention Force of O’ring Attachment: An in Vitro Study

Abstract: The aim of this study was to evaluate the effect of cleaning solutions on the retention force of o-ring-type overdenture attachments. The effect of four solutions on nitrile rings were evaluated: Cepacol (C), Cepacol with fluoride (CF), Listerine (L) and 0.05% sodium hypochlorite (SH); deionized water (DW) was used as a control. Matrices containing two implants and abutments and acrylic specimens with the metal capsules were obtained and divided into the groups. A simulation of 90 overnight immersions (8 h) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 34 publications
0
8
0
10
Order By: Relevance
“…Despite that, this effect was not significant when observed at acidic and neutral pH [ 40 ]. Furthermore, a recent study has demonstrated that the exposure to commercial mouthwash reduced the tensile strength of nitrile O-rings used for overdenture attachment [ 20 ]. Changes in surface morphology following the exposure to a certain type of cleaning solution were also reported [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite that, this effect was not significant when observed at acidic and neutral pH [ 40 ]. Furthermore, a recent study has demonstrated that the exposure to commercial mouthwash reduced the tensile strength of nitrile O-rings used for overdenture attachment [ 20 ]. Changes in surface morphology following the exposure to a certain type of cleaning solution were also reported [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study has demonstrated that the exposure to commercial mouthwash reduced the tensile strength of nitrile O-rings used for overdenture attachment [ 20 ]. Changes in surface morphology following the exposure to a certain type of cleaning solution were also reported [ 20 ]. However, the influence of bleaching agents at the concentration used in commercial mouthwashes appeared to be not as significant, based on the findings from another study [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A hipótese nula testada foi que os métodos de higienização avaliados não alterariam os diâmetros interno e externo dos o'rings e não provocariam diferença na força de retenção durante os diferentes tempos de análise. Cada grupo, referente a cada método de higiene foi composto por 6 corpos de prova (FELIPUCCI et al, 2020) e em cada corpo de prova foram colocados 2 o'rings (simulando o que ocorre na maioria dos casos de overdentures).…”
Section: Hipótese Nulaunclassified
“…Em casos de overdentures, não há ainda um protocolo de higienização estabelecido. Há relatos que a alteração da retenção das cápsulas pode ocorrer não somente devido ao uso prolongado do conjunto macho e fêmea (KARABUDA; YALTRK; BAYRAKTAR, 2008;LERTSURIYAKARN;PALANUWECH, 2020), ciclos de inserção e remoção da prótese (BONACHELA et al, 2003;YOU et al, 2011;KÜRKCÜOǦLU et al, 2016;CHIU et al, 2017;KANG et al, 2019;FELIPUCCI et al, 2020), temperatura da água (CHIU et al, 2017) mas também devido ao emprego de soluções higienizadoras (VARGHESE et al, 2007;NGUYEN et al, 2010;YOU et al, 2011;WATCHARAPICHAT et al, 2014;DERAFSHI et al, 2015;KÜRKCÜOǦLU et al, 2016;KHODADADKASHI et al, 2019;AYYILDIZ et al, 2020;FELIPUCCI et al, 2020;KÜÇÜKEKENCI;DEDE;ÇELIK, 2021). Existe uma grande dificuldade em avaliar as características físicas e mecânicas das cápsulas, visto que, são estruturas pequenas e que sua composição é diferente de acordo com a marca comercial utilizada (FELIPUCCI et al, 2020;KÜÇÜKEKENCI;DEDE;ÇELIK, 2021).…”
Section: Introdução 1 Introduçãounclassified